(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Cognitive Radio has been the solution for the problem of underutilization of radio spectrum in which cognitive radio devices intelligently sense and exploit the part of spectrum. Hybrid Cognitive Radio Network is useful to improve the security and reliability of the network. Hybrid cognitive radio network jointly utilize both the cognitive and licensed radio networks. This paper analyses the performance of Hybrid Cognitive Relay network for single relay and multiple relay under AWGN and Rayleigh fading channels. The performance metrics such as Capacity, Bit error rate and Spectral efficiency are formulated and numerical simulations by using MATLAB are performed. This analysis is helpful in determining the Capacity and Bit error rate for optimum usage of power and bandwidth is better. This analysis is also helpful to compare the result of single relay and multiple relay hybrid graphs.